2019
DOI: 10.3390/membranes9090110
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Evaluation of Graphene Membrane Performance for Hydrogen Separation Using Molecular Dynamic Simulation

Abstract: The main purposes of this study are to evaluate the performance of graphene membranes in the separation/purification of hydrogen from nitrogen from a theoretical point of view using the molecular dynamic (MD) simulation method, and to present details about molecular mechanisms of selective gas diffusion through nanoscale pores of graphene membranes at the simulated set conditions. On the other hand, permeance and perm-selectivity are two significant parameters of such a membrane that can be controlled by sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The H 2 -permselectivities of the composite membrane measured in this study were briefly compared with those recently reported for other membranes composed of various materials systems, and their H 2 permeation data with α(H 2 /X) (X = N 2 (0.364 nm) [ 51 ] or O 2 (0.346 nm) [ 51 ]) measured under the dry condition at T ≤ 50 °C are listed in Table 3 [ 18 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Among them, novel ultrathin (9 nm thickness) graphene oxide membrane formed on an anodic oxidized alumina support (#09) exhibited a H 2 permeance of approximately 1 × 10 −7 mol m −2 s −1 Pa −1 with α(H 2 /N 2 ) of 900 at 20 °C [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The H 2 -permselectivities of the composite membrane measured in this study were briefly compared with those recently reported for other membranes composed of various materials systems, and their H 2 permeation data with α(H 2 /X) (X = N 2 (0.364 nm) [ 51 ] or O 2 (0.346 nm) [ 51 ]) measured under the dry condition at T ≤ 50 °C are listed in Table 3 [ 18 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Among them, novel ultrathin (9 nm thickness) graphene oxide membrane formed on an anodic oxidized alumina support (#09) exhibited a H 2 permeance of approximately 1 × 10 −7 mol m −2 s −1 Pa −1 with α(H 2 /N 2 ) of 900 at 20 °C [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%